The Beach Aquifer Microbiome: Research Gaps and Data Needs - Archana, Anand; Francis, Christopher A.; Boehm, Alexandria B. (Frontiers in Environmental Science, 2021)
Beach aquifers, located in the subsurface of sandy beaches, are unique ecosystems with steep chemical and physical gradients resulting from the mixing of terrestrial fresh groundwater and saline groundwater from the sea. While work has rapidly progressed to understand the physics and chemistry in this environment, much less is known about the microorganisms present despite the fact that they are responsible for vital biogeochemical processes. This paper presents a review of the current state of knowledge of microbes within beach aquifers and the mechanisms that control the beach aquifer microbiome. We review literature describing the distribution and diversity of microorganisms in the freshwater-saltwater mixing zone of beach aquifers, and identify just 12 papers. We highlight knowledge gaps, as well as future research directions: The understanding of beach aquifer microorganisms is informed primarily by 16S ribosomal RNA gene sequences. Metagenomics and metatranscriptomics have not yet been applied but are promising approaches for elucidating key metabolic and ecological roles of microbes in this environment. Additionally, variability in field sampling and analytical methods restrict comparison of data across studies and geographic locations. Further, documented evidence on the migration of microbes within the beach aquifer is limited. Taking into account the physical transport of microbes through sand by flowing groundwater may be critical for understanding the structure and dynamics of microbial communities. Quantitative measurements of rates of elemental cycling in the context of microbial diversity need further investigation, in order to understand the roles of microbes in mediating biogeochemical fluxes from the beach aquifer to the coastal ocean. Lastly, understanding the current state of beach aquifers in regulating carbon stocks is critical to foster a better understanding of the contribution of the beach aquifer microbiome to global climate models.